Relación entre motivación y el rendimiento académico en estudiantes de grado 11 de la Institución Educativa Inem José Eustasio Rivera De Leticia-Amazonas (2021)
First of all, motivation is a fundamental state of the human being for life, without it there would be no motor that generates a behavior. Therefore, it has been defined as an internal state or condition that activates, directs and maintains a behavior (Schunk, 1996). As stated by said author, it can be said that a motivated student will be very likely to get good grades, because he will always be looking for ways to learn and strengthen his knowledge acquired in the classroom. Being motivated or willing to study is as important or more important than intelligence to achieve good grades. (Ramos, 2003). As a consequence, it is necessary that students are always motivated, since this will drive them to solve problems or difficulties that arise in the educational field.